THE CONCEPT OF “HOME” IN ENGLISH AND UZBEK CULTURES: A LINGUISTIC PERSPECTIVE (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
The notion of home is one of the most deeply rooted cultural and linguistic concepts in any society. Although universal at a conceptual level, its semantic scope, emotional associations, and cultural symbolism differ significantly across languages. This article explores how the concept of “home” is represented, interpreted, and linguistically encoded in English and Uzbek cultures. Drawing on lexical semantics, cultural linguistics, and discourse analysis, it examines the meanings, connotations, idioms, metaphors, and cultural values associated with the English term home and its Uzbek equivalents such as uy, ona diyor, Vatan, oila, and tinch o‘choq. Special attention is given to familial structure, individualism versus collectivism, and historical worldviews embedded in linguistic usage. The findings reveal that while English conceptualizes home primarily as a private personal space emphasizing individuality and emotional comfort, Uzbek culture frames home as a collective, intergenerational, and sacred sphere that extends beyond the household to notions of homeland and ancestry. These cross-cultural insights highlight how language mirrors cultural identity and how cultural patterns, in turn, shape linguistic expression.